Extra-corporeal membrane oxygenation and emergency C-section for a pregnant COVID-19 positive patient. (March 2023) - Quintero, Alejandro; Vinck, Eric E; Pérez, Luz E; Escobar, José J; Rendón, Juan C; Uribe, Juan D
Introduction: Data on extra-corporeal membrane oxygenation (ECMO) therapy for pregnant patients with Coronavirus 2019 (COVID-19) infection are limited. Here we report a case of an emergency cesarean section performed while the COVID-19 positive mother was on ECMO support. Case report: A 36-year-old COVID-19 positive patient at 26 weeks gestational age presented with respiratory failure requiring extra-corporeal membrane oxygenation therapy. Nine days later fetal distress demanded an emergency C-section. After 5 weeks on ECMO, the patient was weaned off. Both mother and child were discharged. Discussion: The decision to perform an urgent C-section is one that requires meticulous thought from the attending team. Pulmonary maturation is key as pregnancy may need to be terminated at any time during ECMO. Conclusion: Data on ECMO support for pregnant patients with COVID-19 infection are scarce. Best results can be achieved ensuring adequate anticoagulation, meticulous choice of cannulas, continued fetal monitoring, early lung maturation, and precision timing of delivery.